โครงการการบูรณาการศาสตร์เพื่อการพัฒนาพื้นที่ อำเภอครบุรี จังหวัดนครราชสีมา ด้วยการใช้หลักปรัชญาเศรษฐกิจพอเพียง - เอกรัตน์ เอกศาสตร์, Ekkarat Ekkasart / (Naresuan University Journal: Science and Technology (NUJST); Vol 21 No 2 (2013): May-August 2013, 2014)
การศึกษาครั้งนี้มีวัตถุประสงค์เพื่อสร้างความรู้และความเข้าใจหลักปรัชญาเศรษฐกิจพอเพียงให้กับประชาชนในพื้นที่อำเภอครบุรี จังหวัดนครราชสีมา และเพื่อจัดทำแผนพัฒนาพื้นที่อำเภอครบุรี จังหวัดนครราชสีมาภายใต้หลักปรัชญาเศรษฐกิจพอเพียง โดยความร่วมมือระหว่างมหาวิทยาลัยราชภัฏนครราชสีมากับภาคีในพื้นที่ โดยมีตำบลสระว่านพระยา อำเภอครบุรี จังหวัดนครราชสีมาเป็นพื้นที่วิจัย ในด้านของการเก็บรวบรวมข้อมูลมีทั้งข้อมูลปฐมภูมิด้วยการสำรวจภาคสนาม การประชุมกลุ่มการฝึกอบรมการเข้าค่าย การจัดเวทีถามและตอบการสัมภาษณ์ การประเมินผล การจัดเวทีแลกเปลี่ยนเรียนรู้ และการลงพื้นที่เพื่อนิเทศ ติดตาม และให้คำปรึกษา และข้อมูลทุติยภูมิจากเอกสารของหน่วยงานต่างๆ ที่เกี่ยวข้องในพื้นที่ สำหรับการวิเคราะห์ข้อมูลใช้การวิเคราะห์เนื้อหาแบบพรรณนา และการวิเคราะห์เชิงปริมาณ ผลการศึกษาในส่วนของการสร้างความรู้และความเข้าใจหลักปรัชญาเศรษฐกิจพอเพียงให้กับประชาชนในพื้นที่อำเภอครบุรี จังหวัดนครราชสีมาพบว่า มี3ขั้นตอน โดยขั้นตอนแรก คือ การเตรียมความพร้อมในการสร้างความรู้และความเข้าใจหลักปรัชญาเศรษฐกิจพอเพียงด้วยการสำรวจภาคสนามเพื่อศึกษาบริบทเบื้องต้นของพื้นที่ การสำรวจภาคสนามเพื่อศึกษาพื้นฐานองค์ความรู้ของประชาชนในพื้นที่ด้านปรัชญาเศรษฐกิจพอเพียง และการประชุมกลุ่มเพื่อเตรียมการเพิ่มเติมความรู้และความเข้าใจในด้านปรัชญาเศรษฐกิจพอเพียง ขั้นตอนที่สอง คือขั้นตอนการให้ความรู้และความเข้าใจหลักปรัชญาเศรษฐกิจพอเพียงด้วยการฝึกอบรมในภาคทฤษฎีการเข้าค่ายฝึกภาคปฏิบัติและการจัดเวทีถาม และตอบปัญหา และขั้นตอนที่สาม คือ ขั้นตอนการประเมินผลการสร้างความรู้ และความเข้าใจหลักปรัชญาเศรษฐกิจพอเพียงด้วยการใช้แบบประเมินความพึงพอใจในการสร้างความรู้และความเข้าใจหลักปรัชญาเศรษฐกิจพอเพียง ซึ่งพบว่ากลุ่มตัวอย่างมีความพึงพอใจระดับมาก (x =4.18 และ S.D.=0.09) และการประเมินผลด้วยแบบทดสอบซึ่งพบว่าประชาชนมีองค์ความรู้ด้านปรัชญาเศรษฐกิจพอเพียงถึงร้อยละ 89.28 เพิ่มขึ้นจากเดิม ร้อยละ 32.18 ในส่วนของการศึกษาการจัดทำแผนพัฒนาพื้นที่อำเภอครบุรี จังหวัดนครราชสีมาภายใต้หลักปรัชญาเศรษฐกิจพอเพียง โดยความร่วมมือระหว่างมหาวิทยาลัยราชภัฏนครราชสีมากับภาคีในพื้นที่ มีจำนวน 3 ขั้นตอน โดยขั้นตอนแรก คือการศึกษาบริบทของพื้นที่ จำนวน 4 ด้าน คือทรัพยากรธรรมชาติและสิ่งแวดล้อม เศรษฐกิจ สังคม และโครงสร้างพื้นฐาน ขั้นตอนที่สอง คือ การจัดทำแผนพัฒนาพื้นที่ภายใต้หลักปรัชญาเศรษฐกิจพอเพียงด้วยการจัดเวทีเพื่อจัดทำแผนการทำงาน การจัดเวทีแลกเปลี่ยนเรียนรู้การจัดทำแผนการทำงานร่วมกัน และการลงพื้นที่เพื่อนิเทศ ติดตาม และให้คำปรึกษา ผลที่ได้รับคือประชาชนในพื้นที่ได้แผนพัฒนาพื้นที่ตำบลสระว่านพระยา อำเภอครบุรี จังหวัดนครราชสีมา ภายใต้หลักปรัชญาเศรษฐกิจพอเพียง อันเกิดจากกระบวนการมีส่วนร่วมของประชาชนในพื้นที่ จำนวน 2 ระดับ คือ ระดับบุคคล/ครัวเรือน และระดับกลุ่ม/ชุมชน และขั้นตอนที่สาม คือขั้นตอนการลงพื้นที่เพื่อนำแผนพัฒนาพื้นที่ภายใต้หลักปรัชญาเศรษฐกิจพอเพียงไปเผยแพร่ซึ่งประกอบด้วยกิจกรรมการประชาสัมพันธ์แผนงาน/โครงการกับประชาชนและหน่วยงานต่างๆในพื้นที่การขอความอนุเคราะห์ผู้รับผิดชอบหลักในแต่ละกิจกรรม การคัดเลือกตัวแทนภาคครัวเรือนเพื่อดำเนินกิจกรรมตามแผนพัฒนาระดับบุคคล/ครัวเรือนการจัดทำโครงการนำร่องภายใต้หลักปรัชญาเศรษฐกิจพอเพียงตามแผนพัฒนาระดับกลุ่ม/ชุมชน และการเตรียมการในการประเมินผลการจัดทำแผนพัฒนาจากหน่วยงานกลาง คำสำคัญ: การบูรณาการศาสตร์ การพัฒนาพื้นที่ หลักปรัชญาเศรษฐกิจพอเพียง This particular study had been proposed in order to encourage villagers’ insightful understanding and knowledge towards Sufficiency Economy Philosophy in Khonburi district, Nakhon Ratchasima as well as to establish Khonburi Area Development Plan which Sufficiency Economy Philosophy under the coordination between Nakhon Ratchasima Ratchabhat University and concerning parties in particular area. Srawanphraya subdistrict, Khonburi was chosen as the targeted area to conduct the research. Data collection was collected in both primary and secondary data forms. Primary data; for example, included survey field practice, focus group, training session, camp, evaluation process, public forum to exchange ideas, field trip for acknowledging, following up and giving possible advice to villagers. Moreover, secondary data included related document from concerning organizations in the area. In terms of data analysis, the study employed descriptive content analysis and Quantitative Analysis. The result relating to the understanding and knowledge towards Sufficiency Economy Philosophy for villagers in Khonburi district, Nakhon Ratchasima was revealed that there were 3 steps in this process; first, the preparation step prior to construct insightful understanding and knowledge towards Sufficiency Economy Philosophy by applying survey field practice in order to explore general basic context in the area, to check villagers’ knowledge about Sufficiency Economy Philosophy and to launch the focus group for preparing which aspects towards Sufficiency Economy Philosophy do they have to add up for the villagers. Second step was to educate villagers with Sufficiency Economy Philosophy’s knowledge and understanding by providing them a practical camp, training session and a meeting relating to Sufficiency Economy Philosophy. And finally, the step of evaluating performances of providing knowledge and insightful understanding towards Sufficiency Economy Philosophy by employing questionnaire to investigate respondents’ satisfactory and the research found that the sample group was pleased with this Sufficiency Economy Philosophy’s learning processes at the highest level ( x =4.18 and S.D.=0.09). In terms of taking a test about Sufficiency Economy Philosophy’s understanding, the result was found that after villagers had been successfully constructed knowledge towards Sufficiency Economy Philosophy, they possessed insightful understanding in specific issue at 89.28% which increased from earlier result by 32.18% When considering Khonburi Development Plan by adopting Sufficiency Economy Philosophy under the coordination between Nakhon Ratchasima Ratchabhat University and concerning parties in particular area, it was found that there were also 3 steps ; first, the step of exploring general basic context in the Srawanphraya subdistrict area in 4 categories which were natural resources and environment, economics, society and basic infrastructure. Next step was to establish Srawanphraya Development Plan by adopting Sufficiency Economy Philosophy by holding a public forum to discuss a plan relating to 4 aspects; resources, economics, society and politics and a forum to share knowledge about the plan. Moreover, in this step, there was also a field operation to follow up and give possible advice. The result in this step showed that villagers had finally finished with the Srawanphraya Development Plan by adopting Sufficiency Economy Philosophy in terms of moderation, reasonability, self-immunity, knowledge and morality conditions which were contributed by participatory process of 2 separated levels of villagers in the area; person or a household level and a group or community level. Finally, the last step was to apply the Development Plan under the Sufficiency Economy Philosophy in the real context. In this step, there were public relation activities to introduce the plan to villagers and organizations in the area, finding sponsors and supporters for each activity from government, select representatives from household to do the activities according to the plan in person or a household level, piloting the project dealing with Sufficiency Economy Philosophy in a group or community level and evaluating process towards the running project from both organizations inside and outside the area of Khonburi. From all resulted showed earlier, it meant that Srawanphraya subdistrict, Khonburi, Nakhon Ratchasima would have stable economic and social structures which contribute to sustainable lives of villagers according to local economics and villagers altogether live with peace and care. Keywords: Integrated Sciences, Area Development, Sufficiency Economy Philosophy
Keywords: การบูรณาการศาสตร์ การพัฒนาพื้นที่ หลักปรัชญาเศรษฐกิจพอเพียง Integrated Sciences, Area Development, Sufficiency Economy Philosophy